Citation Analysis of Journal Manajemen Stratejik dan Simulasi Bisnis 2020 - 2022 - Pringati Singarimbun (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
This study aims to determine the distribution of google scholar citations of the Manajemen Stratejik dan Simulasi Bisnis in the period 2020 – 2023. Citation distribution data is extracted using  Publish or Perish 8 software, the results of which are used as a basis to describe the distribution of citations to the journal as a whole and citations to each article that has been published and indexed by Google Scholar. The results of this research are expected to help journal managers in developing and improving the quality of journals so that they have a real impact on the progress of science according to the scope of the  journal.